Gap Assessment on Capacity Building in Climate Smart Agriculture and Climate Information Services in Tertiary Institutions in Ghana, Mali And Senegal - Agyare, Wilson Agyei; Amponsah, William; Bessah, Enoch; Diallo, Yacouba; Ndiaye, Mohamed BO; Koné, Daouda; Segnon, Alcade C.; Zougmoré, Robert B. (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) Project builds on the initiatives and achievements under the CGIAR Research Program on the Climate Change, Agriculture and Food Security (CCAFS) in Africa. With a focus on climate-smart agriculture (CSA) technologies and on climate information services (CIS), the AICCRA project includes an important capacity development component for the benefit of six (6) countries in Africa. Given that West African Science Service Centre on Climate Change and Adapted Land Use (WASCAL) is a large-scale education and research-focused climate service institution operating through 12 graduate schools across West Africa, together with the African Regional Universities Forum for Capacity Building in Agriculture (RUFORUM) member universities in Ghana, Mali and Senegal, is working to develop curricula and training materials on CIS and CSA. The output will be made widely accessible to West Africa stakeholders through WASCAL and RUFORUM university/academia networks. CIS and CSA concepts are coming up with emerging areas of research that has to take into account indigenous knowledge and early dissemination in the education ladder. Capacity building in these areas will provide research and evidence-based solutions to ensure food security and build resilience of farming systems in the face of climate change in sub-Saharan Africa. WASCAL conducted gap assessment in capacity building for the development of curricula or training programmes in CIS and CSA in tertiary institutions in Ghana, Mali and Senegal. Responses were sought and obtained from 52 academic staffs from universities in Ghana (29), Mali (9) and Senegal (14). The background and expertise of the respondents were in climate change, agriculture and environmental science from eight (8), four (4) and six (6) institutions in Ghana, Mali and Senegal, respectively. Data were sought through questionnaires, interviews and/or focused group discussion. Descriptive statistics represented by percentages and frequencies were used to analyze the quantitative data whereas content and thematic analyses were used to analyze the qualitative data. The thematic analysis categorized the responses into eight (8) broad themes that were analyzed in details. These themes included (i) expertise of respondents (ii) knowledge on the concepts of CIS and CSA (iii) access to climate information (iv) beneficiaries and stakeholders of climate information (v) curricula contents for CIS and CSA training materials and (vi) capacity building and mode of delivery. Summary of the focused group discussion in five (5) universities in Ghana, three (3) universities in Mali and one (1) university in Senegal are also presented. The key findings of this study are (i) introduce CIS and CSA at the basic level of education and (ii) curricula for CIS should focus on data analysis, packaging and dissemination; whereas CSA should focus on the technologies.